Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
bài 1
a) \(M=\sin^242^o+\sin^243^o+\sin^244^o+\sin^245^o+\sin^246^o+\sin^247^o+\sin^248^o\)
\(M=\cos^248^o+\cos^247^o+\cos^246^o+\sin^245^o+\sin^246^o+\sin^247^o+\sin^248^o\)
\(M=\left(\sin^248^o+\cos^248^o\right)+\left(\sin^247^o+\cos^247^o\right)+\left(\sin^246^o+\cos^246^o\right)+\sin^245^o\)
\(M=1+1+1+0,5\)
\(M=3,5\)
bài 1
b) \(N=\cos^215^o-\cos^225^o+\cos^235^o-\cos^245^o+\cos^255^o-\cos^265^o+\cos^275^o\)
\(N=\sin^275^o-\sin^265^o+\sin^255^o-\cos^245^o+\cos^255^o-\cos^265^o+\cos^275^o\)
\(N=\left(\sin^275^o+\cos^275^o\right)-\left(\sin^265^o+\cos^265^o\right)+\left(\sin^255^o+\cos^255^o\right)-\cos^245^o\)
\(N=1-1+1-0,5\)
\(N=0,5\)
c)
\(\cos\left(x\right)^4+\sin\left(x\right)^2\cos\left(x\right)^2+\sin\left(x\right)^2\\ =\left(\cos\left(x\right)^2+\sin\left(x\right)^2\right)\cos\left(x\right)^2+\sin\left(x\right)^2\\ =\cos\left(x\right)^2+\sin\left(x\right)^2\\ =1\)
\(\cos\left(x\right)^4-\sin\left(x\right)^4+2\sin\left(x\right)^2\\ =\left(\cos\left(x\right)^2-\sin\left(x\right)^2\right)\left(\cos\left(x\right)^2+\sin\left(x\right)^2\right)+2\sin\left(x\right)^2\\ =\cos\left(2x\right)\cdot1+2\sin\left(x\right)^2\\ =\cos\left(x\right)^2-\sin\left(x\right)^2+2\sin\left(x\right)^2\\ =\cos\left(x\right)^2+\sin\left(x\right)^2\\ =1\)
a) 1- \(sin^2\alpha\)= \(cos^2\alpha\)
b) (\(1-cos\alpha\))(\(1+cos\alpha\)) = 1 - cos2\(\alpha\) = sin2\(\alpha\)
c) 1 + cos2\(\alpha\) + sin2\(\alpha\) = \(1+1=2\)
d) sin\(\alpha\) - sin\(\alpha.cos^2\alpha\)
= \(sin\alpha\left(1-cos^2\alpha\right)=sin\alpha.sin^2\alpha=sin^3\alpha\)
e) \(sin^4\alpha+cos^4\alpha+2sin^2\alpha.cos^2\alpha\)
= \(\left(sin^2\alpha\right)^2+2sin^2\alpha.cos^2\alpha+\left(cos^2\alpha\right)^2\)
= \(\left(sin^2\alpha+cos^2\alpha\right)^2=1^2=1\)
f) \(tan^2\alpha-sin^2\alpha.tan^2\alpha\)
= \(tan^2\alpha\left(1-sin^2\alpha\right)=tan^2\alpha.cos^2\alpha=sin^2\alpha\)
g) \(cos^2\alpha+tan^2\alpha.cos^2\alpha\)
= \(cos^2\alpha\left(1+tan^2\alpha\right)=cos^2\alpha.\dfrac{1}{cos^2\alpha}=1\)
h) \(tan^2\alpha\left(2cos^2\alpha+sin^2\alpha-1\right)\)
= \(tan^2\alpha\left[cos^2\alpha+\left(cos^2\alpha+sin^2\alpha\right)-1\right]\)
= \(tan^2\alpha\left(cos^2\alpha+1-1\right)\)
= \(tan^2\alpha.cos^2\alpha=sin^2\alpha\)
A = sin6x + cos6x +sin4x +cos4x + 5sin2x.cos2x
\(=\left(\sin^2x+\cos^2x\right)\left(\sin^4x-\sin^2x\cos^2x+\cos^4x\right)+\sin^4x+\cos^4x+5\sin^2x\cos^2x\)
\(=2\left(\sin^2x+2\sin^2x\cos^2x+\cos^2x\right)\)
\(=2\)